REVOLUTION, MODERNITY, AND THE POTENTIAL OF NARRATIVES: SELF‐DETERMINATION AND HISTORY IN GOETHE'S WORKS OF THE 1790s. (9th September 2013) - Eriksson, Birgit
ABSTRACT: This article investigates the impact of the French Revolution on Goethe's narrative works in the mid‐1790s. I argue that the reductive interpretation of Goethe's attitude to the Revolution as distant and reluctant ignores the formal and thematic impact of the Revolution on his prose works. Similarly, we lose important perspectives when reducing German intellectual life of the late eighteenth century to apolitical inwardness. The Revolution had an impact, also in the German context, and Goethe's literary works were significantly affected by it. Working in various literary genres, he investigated and experimented with some of the fundamental challenges of the Revolution and the modern era, especially those regarding self‐determination, community, and the nexus between individual and shared history. Following a brief sketch of how these issues looked from a German perspective, I will focus on Goethe's treatment of them in two literary works from the mid‐1790s: his cycle of novellas, Unterhaltungen deutscher Ausgewanderten (1795) and his Bildungsroman, Wilhelm Meisters Lehrjahre (1795–6).